A qualitative interpretive meta-synthesis of social workers' experience in end-of-life care. (March 2023) - Dewar, Simone; Mensinga, Jo; Redman-MacLaren, Michelle; Johns, Lise
Summary: Social workers are an integral part of end-of-life (EOL) care interdisciplinary services and provide comprehensive psychosocial support to dying people. However, despite the rewards, EOL care social work is wrought with challenges. There is currently limited research into the experience of EOL care social workers. Therefore, this qualitative interpretive meta-synthesis (QIMS) study examines the experience of EOL care social workers as revealed in existing literature. The QIMS methodology was used to synthesize and interpret findings from four original qualitative studies to elicit an in-depth response to the research question: What is the experience of social workers who work in EOL care? Findings: The theme "EOL care social work is a privilege and a struggle" emerged, with six associated contributing factors: Privilege—(1) death is sacrosanct, (2) death is an opportunity for growth and healing, and (3) the religious/spiritual element of EOL care. Struggle—(1) ongoing pain and heightened emotions, (2) conflict of values, and (3) contextual challenges. This QIMS study serves as a preliminary phase to a subsequent, larger study. Applications: This QIMS study provides a foundation for further narrative research into the experience of EOL care social workers. In addition, findings from this QIMS study highlights areas for further attention to foster the well-being of EOL care social workers. Finally, findings from this QIMS study could augment relevant EOL care content in undergraduate social work education.